Antibiotic prophylaxis versus no antibiotic prophylaxis in transperineal prostate biopsies (NORAPP): a randomised, open-label, non-inferiority trial. Issue 10 (October 2022) - Jacewicz, Maciej; Günzel, Karsten; Rud, Erik; Sandbæk, Gunnar; Magheli, Ahmed; Busch, Jonas; Hinz, Stefan; Baco, Eduard
Summary: Background: The benefit of antibiotic prophylaxis is uncertain when performing transperineal prostate biopsies. Judicious use of antibiotics is required as antimicrobial resistance increases worldwide. We aimed to assess whether antibiotic prophylaxis can be omitted when performing transperineal prostate biopsies under local anaesthesia as an outpatient procedure. Methods: In this randomised, open-label, non-inferiority trial, we aimed to enrol all patients with a suspicion of prostate cancer undergoing transperineal prostate biopsies at two hospitals in Norway and Germany. Patients with a high risk of infection or ongoing infection were excluded. Patients were randomised (1:1) to receive intramuscular (in Norway) or intravenous (in Germany) 1·5 g cefuroxime antibiotic prophylaxis or not. Follow-up assessments were done after 2 weeks and 2 months. The primary outcome was rate of sepsis or urinary tract infections requiring hospitalisation within 2 months. The secondary outcome was the rate of urinary tract infections not requiring hospitalisation. These outcomes were assessed in all eligible randomly allocated participants with a prespecified non-inferiority margin of 4%. Biopsies were performed using an MRI–transrectal ultrasound fusion transperineal technique under local anaesthesia. Patients with a positive MRI underwent 2–4 biopsies per target; in addition, 8–12 systematic biopsies were performed in biopsy naive and MRI-negative patients. This study is registered with ClinicalTrials.gov, NCT04146142 . Findings: Between Nov 11, 2019, and Feb 23, 2021, 792 patients were referred for biopsy, of whom 555 (70%) were randomly allocated to treatment groups. 277 (50%) patients received antibiotic prophylaxis and 276 (50%) did not; two (<1%) patients were excluded after randomisation because of unknown allergy to study drug. Sepsis or urinary tract infections requiring hospitalisation occurred in no patients given antibiotic prophylaxis (0%, 95% CI 0 to 1·37) or not given antibiotic prophylaxis (0%, 0 to 1·37; difference 0% [95% CI –1·37 to 1·37]). Urinary tract infections not requiring hospitalisation occurred in one patient given antibiotic prophylaxis (0·36%, 95% CI 0·01 to 2·00) and three patients not given antibiotic prophylaxis (1·09%, 0·37 to 3·15; difference 0·73% [95% CI –1·08 to 2·81]). The number needed to treat with antibiotic prophylaxis to avoid one infection was 137. Interpretation: The non-inferiority margin of 4% was not exceeded, suggesting rates of infections were not higher in patients not receiving antibiotic prophylaxis before transperineal prostate biopsy than in those receiving it. Therefore, antibiotic prophylaxis might be omitted in this population. Funding: Oslo University Hospital, Oslo, Norway and Vivantes Klinikum Am Urban, Berlin, Germany.